A red luminescent Eu3+ doped conjugated microporous polymer for highly sensitive and selective detection of aluminum ions. Issue 3 (18th January 2021) - Niu, Tianhui; Yao, Chan; Xie, Wei; Zhang, Shuran; Xu, Yanhong
Abstract : A Eu 3+ doped-CMP composite can be used as a chemosensor for highly sensitive and selective detection of Al 3+ . Abstract : A red luminescent europium ion (Eu 3+ ) doped CMP composite (Phen-Eu@BPPD-CMP) was prepared for the first time, in which Eu 3+ ions coordinated with diketone moieties and 1, 10-phenanthroline (Phen). The fluorescent composite could be used as a chemosensor for highly sensitive and selective detection of aluminum ions (Al 3+ ). Compared to a linear polymer analogue (Phen-Eu@BPPD-LP), Eu 3+ -doped CMP without Phen groups (Eu@BPPD-CMP), and a Eu(OAc)3 -BPPD-CMP mixture, Phen-Eu@BPPD-CMP allowed for the rapid detection of Al 3+, which could have been caused by the mutual promotion of π-conjugated skeletons and the complementary coordination of Phen groups to facilitate the sensing process and improve the response to Al 3+ ions.